2016
DOI: 10.1007/s40808-016-0241-4
|View full text |Cite
|
Sign up to set email alerts
|

Drilling fluid loss control via implementing the FMI and DSI logs to protect environment

Abstract: Implementing the drilling fluids in drilling operations is of paramount importance owing to the variety of applications and benefits they provide. Materials added to drilling fluid could cause numerous environmental problems in soil and water resources, and these problems are more pronounced in offshore as compared to land fields. Heavy metals such as mercury, barium, arsenic, lead, and nickel exist in drilling fluid, which bring detrimental damages to the environment. Moreover, heavy metals exist in oil-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Understanding in-situ stress is essential for oil and gas exploration and production, particularly for wellbore stability, hydraulic fracturing, flooding patterns, and fluid flow in fractured reservoirs [1][2][3][4][5]. In-situ stress can be detected using various theoretical, experimental, and field methods, such as overcoring, hydraulic fracturing, focal-mechanism solution, borehole breakout, and geological analysis [6][7][8]. It is challenging to employ overcoring and hydraulic fracture procedures at deep depths where there may be violent breakouts, high pressures, or high temperatures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding in-situ stress is essential for oil and gas exploration and production, particularly for wellbore stability, hydraulic fracturing, flooding patterns, and fluid flow in fractured reservoirs [1][2][3][4][5]. In-situ stress can be detected using various theoretical, experimental, and field methods, such as overcoring, hydraulic fracturing, focal-mechanism solution, borehole breakout, and geological analysis [6][7][8]. It is challenging to employ overcoring and hydraulic fracture procedures at deep depths where there may be violent breakouts, high pressures, or high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that for a vertical or nearly vertical well, the orientation of BOs reflects the direction of the minimum horizontal principal stress, and that of DIFs indicates the direction of the highest horizontal principal stress [10][11][12][13]. Consequently, the identification of BOs and DIFs associated with the in-situ maximum horizontal stress and the directions of the tremendous horizontal stress have been widely accomplished using borehole image logs [7,14,15]. Due to the advancement of borehole electrical imaging technology, geoscientists now have access to valuable high-resolution data on the features and specifics of the formations that exploration wells have been able to intercept [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The "X" field, as a northern extension of Qatar's North Gas Field, is located in the Persian Gulf about 175 km from Kish Island and 105 km from Qatar [29] (Fig. 1).…”
Section: Geological Settingmentioning
confidence: 99%
“…The log data were analyzed and evaluated using the MULTIMIN interpretation method for all formation units in well A [29]. Generally, the amount of shale has been neglected due to its low percentages from the gamma ray (GR) log of K1, K2, K3, and K4 units.…”
Section: Petrophysical Analysismentioning
confidence: 99%
See 1 more Smart Citation